The Genistein Daidzein in Kudzu Root (Pueraria lobata) Extract Decreased Malondialdehyde Plasma Levels in Hypoestrogenic Rats - Nany Nita Noviana; Nina Rini Suprobo; I Wayan Arsana Wiyasa (Asian Journal of Health Research, 2022)
Introduction: Menopause can reduce women's quality of life and cause health issues. The decline in estrogen during menopause is thought to trigger oxidative stress. When the creation of antioxidants does not match the synthesis of reactive oxygen species (ROS) as an antidote, oxidative stress ensues, characterized by malondialdehyde. The aim of the research is to evaluate the effect of the dose of isoflavone genistein daidzein powder in Kudzu root (Pueraria lobata) extract on the decrease in plasma malondialdehyde (MDA) plasma levels in hypoestrogenic rats. Methods: 30 rats Wistar rats were separated into five groups, namely: the control group, the ovariectomy (OVX) group, waited two weeks to produce hypoestrogenic rats. Of the four groups, the positive group was not given a Pueraria lobata powder containing the isoflavones genistein and daidzein (IGD), and the other group was given 15 mg, 30 mg, 60 mg per kg body weight per day, respectively. Twenty-one days later, the mice were killed, and plasma was taken to be checked for MDA levels using spectrophotometry. Results: Genistein Daidzein in kudzu root extract was effective in reducing the oxidative stress. All IGD doses significantly reduced plasma MDA levels. At a dose of 60mg/kg BW, the plasma MDA levels were comparable to those in the control group, it could prevent a significant increase in plasma MDA levels in hypoestrogenic rats. Conclusion: Isoflavone Genistein and Daidzein of kudzu root (Pueraria lobata) extract reduced MDA plasma levels in hypoestrogenic rats.